Penurunan Angka Morbiditas dan Mortalitas Anak Babi yang Diberi Vitamin dan Elektrolit Melalui Air Minum Saat Disapih - Ardana, Ida Bagus Komang (Buletin Veteriner Udayana, 2012)
The present work was aimed to study the effect of oral treatment of piglets with vitaminand electrolyte at the time of weaning on their morbidity and mortality rates. A number of160 piglets at 28 – 35 days of age were randomly allotted into 4 groups. The control group(P0) received only drinking water whereas the treatment groups were supplied with vitaminand electrolyte (Superfite Forte) for 6 hours a day and for 3 consecutive days at variousdosages; treatment group 1 (P1) received 1 gram/l water, P2: 2 gram/l water and P3: 3gram/l water. Apart from that, drinking water was given ad libitum. Observation andrecording of illness and death was carried out every day from the day of weaning till 21days later. The results showed that treatment with vitamin and electrolyte at 1 – 3 gram/lwater significantly reduced the morbidity and mortality rates. Thus, it is recommended thatpiglets at the time of weaning should be supplied with vitamin and electrolyte in order toreduce the morbidity and mortality rates.
Keywords: Piglets at weaning, vitamin and electrolyte, morbidity and mortality rates